Предмет: Математика,
автор: nikitoscha
Нужна помощь в решении, заранее спасибо!
Приложения:
Ответы
Автор ответа:
0
tgβ*ctgβ-sin²α=1-sin²α=cos²α
ctgα/tgα +sin²α+cos²α= ctg²α+1=1/sin²α
(1+ctgα)/(1+tgα)=ctgα
(1+ctgα)-ctgα(1+tgα)/(1+tgα)=0
1+ctgα-ctgα-1=0
0=0
sin(2π-α)/cos(π/2+α)= -sinα/-sinα =1
ctgα/tgα +sin²α+cos²α= ctg²α+1=1/sin²α
(1+ctgα)/(1+tgα)=ctgα
(1+ctgα)-ctgα(1+tgα)/(1+tgα)=0
1+ctgα-ctgα-1=0
0=0
sin(2π-α)/cos(π/2+α)= -sinα/-sinα =1
Похожие вопросы
Предмет: Русский язык,
автор: ai4525541
Предмет: Математика,
автор: Qazx12345678
Предмет: Другие предметы,
автор: sofa190208
Предмет: Математика,
автор: fhgdfh